2019
DOI: 10.23736/s0375-9393.18.13349-9
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin in sepsis: can we find the right dose?

Abstract: Intravenous immunoglobulin (IVIG) administration in sepsis has been surrounded with controversies since the publication of the first international consensus meeting on this potential therapy almost 40 years ago 1 . Researchers called for evaluation of different treatment doses and durations of IVIG treatment in sepsis, when one of the earliest randomised controlled trials (RCTs) showed no effect and higher rate of significant complications in the IVIG group, using 150 mg/kg bolus dose for three consecutive day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Intravenous immunoglobulin is a therapeutic treatment with anti-infective, anti-inflammatory, and immunomodulatory effects ( Hamano et al, 2013 ; Di Rosa et al, 2014 ). Studies showed that intravenous immunoglobulin can serve as an important part of the adjuvant treatment of sepsis, but for 40 years the method is still controversial ( Hamano et al, 2013 ; Di Rosa et al, 2014 ; Szakmany, 2019 ; Jarczak et al, 2020 ). Esen et al found that the injection of immunoglobulin G or a combination of immunoglobulin A and M both exerted neuroprotective effects, which improved the integrity of the BBB, and alleviated the symptoms of sepsis in rats ( Esen et al, 2012 ) ( Figure 2 ).…”
Section: Bbb and Saementioning
confidence: 99%
“…Intravenous immunoglobulin is a therapeutic treatment with anti-infective, anti-inflammatory, and immunomodulatory effects ( Hamano et al, 2013 ; Di Rosa et al, 2014 ). Studies showed that intravenous immunoglobulin can serve as an important part of the adjuvant treatment of sepsis, but for 40 years the method is still controversial ( Hamano et al, 2013 ; Di Rosa et al, 2014 ; Szakmany, 2019 ; Jarczak et al, 2020 ). Esen et al found that the injection of immunoglobulin G or a combination of immunoglobulin A and M both exerted neuroprotective effects, which improved the integrity of the BBB, and alleviated the symptoms of sepsis in rats ( Esen et al, 2012 ) ( Figure 2 ).…”
Section: Bbb and Saementioning
confidence: 99%
“…Sepsis remains a major cause of death worldwide. [1,2] Many studies have been performed to identify or evaluate potential biomarkers not only for early identification of patients with severe sepsis and their timely transfer to the intensive care unit (ICU) for early intervention but also for increasing the accurate prediction of their outcomes.…”
Section: Introductionmentioning
confidence: 99%